The effect of relative humidity and the use of algae-based biostimulants on fruit set, yield and fruit size of arctic bramble (Rubus arcticus) - Tommila, Tero; Palonen, Pauliina (Agricultural and Food Science, 2024)
Arctic bramble is a niche berry crop with highly variable yield and fruit quality, often limited by low fruit set and incomplete fruit development. In this study, we investigated the effects of relative humidity (RH) and algae-based biostimulants on fruit set, yield, fruit weight and the number of drupelets per fruit. In Experiment 1, arctic bramble cvs. ‘Alli’ and ‘Mesma’ were grown in a greenhouse in 40, 60 or 80% RH and pollinated by bumblebees. In Experiments 2 and 3, commercial biostimulant products Kelpak, Cremalga, Kriss and Alginamin were tested on cv. ‘Alli’ in a greenhouse, and an open high tunnel. Fruit set and yield were strongly affected by RH, being highest in either 40% RH for cv. ‘Mesma’ or 60% RH for cv. ‘Alli’, reduced by nearly 50% in 80% RH. Kriss and Alginamin increased fruit weight by as much as 18% but there was no effect on total yield. We conclude that control of relative humidity in greenhouse cultivation, especially to avoid very high RH conditions, can be highly beneficial for arctic bramble, and that algae-based biostimulants show potential to improve fruit weight.